การพัฒนาทักษะการอ่านออกเสียงคำในภาษาไทยของนักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนบ้านทุ่งแต้ ตำบลทุ่งแต้ อำเภอเมือง จังหวัดยโสธร - จันทคง, สมปอง (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This research aimed to study the level of Thai word pronunciation and compare the achievement in developing Thai word pronunciation skills of Secondary 1 st students at Ban Thung Tae School, Thung Tae Sub-district, Mueang District, Yasothon Province. The target group for this study consisted of six Secondary 1 st students during the first semester of the 2024 academic year. The study employed a quasi-experimental research design. The research results found that the first year secondary school students of the academic year 2024, first semester of Ban Thung Tae School, Mueang District, Yasothon Province, had a moderate level of Thai reading skill ability ( µ = 3.03, σ = 0.79) and found that the Thai reading and writing skill practice was effective and had an achievement level of 81.20/82.05, which was in accordance with the set criteria.